Characterization of titanium alloy-hydroxyapatite composite through powder injection molding - Mohd Ikram Ramli,; Farhana Mohd Foudzi,; Abu Bakar Sulong,; Fatin Aqilah Abdul Yazid,; Norhamidi Muhamad,; Hui, David (Penerbit Universiti Kebangsaan Malaysia, 2020)
Powder injection moulding (PIM) is a process that combines the technologies of plastic injection moulding and powder metallurgy. The fabrication of titanium alloy-hydroxyapatite (Ti6Al4V/HA) composite using PIM is still poorly reported due to the difficulties in processing two different materials namely the metal and ceramic. Such promising composite can be proposed as an implant material due to its great properties. Hence, this work aims to characterise the properties of Ti6Al4V/HA composite produced by PIM. In this work, 90 wt% of Ti6Al4V and 10 wt% of HA were mixed with a binder system of 60 wt% palm stearin and 40 wt% polyethylene. The powder loading of the feedstock was 66 vol%. The feedstock with a pseudoplastic flow is preferred in PIM as fewer defects are formed during the injection moulding process. Moreover, the binders are removed in two stages namely the solvent and thermal debinding. Based on the observation, the removal of palm stearin created capillary routes that help to remove polyethylene during thermal debinding. Next, sintering was performed at three different temperatures, which include 1100o C, 1200o C and 1300o C. The heating rate, holding time and cooling rate was set at 3o C/min, 90 min and 6o C/min, respectively. It was found that Ti6Al4V/HA sintered at 1300o C yielded the highest density of 4.13 g/cm3 . In addition, such sintered part also generated the highest flexural and Young’s modulus with the values of 86.4 MPa and 15.04 GPa, respectively. These values are approximately in the range of the physical and mechanical properties of the extant bone-implant.